Stakeholders' Perceptions and Predictions of Stock Exchange Demutualization: The Case of Kuwait Stock Exchange - Aldeehani, Talla M; Bouresli, Amani Kh. (International Journal of Economics and Financial Issues, 2017)
In this paper, we investigate the perceptions of various stakeholders in relation to the benefits stated in the new capital markets authority law (CMAL) to be achieved when Kuwait Stock Exchange (KSE) is demutualized. We use a survey questionnaire to solicit their agreement on the achievement of specific benefits after six years of activation. Factor analysis was used to extract four new constructs from the collected responses. Market harmony is the construct elected to be the independent variable affecting three dependent variables: stability, corporate governance and attractiveness variables. The results indicate that the different stakeholders have the same perception that privatization of KSE will lead to the achievement of all benefits promised. Furthermore, all three dependent variable are found to be significantly affected by market harmony. These results contradict with the results of an earlier study of the same research project on the relationship between firm performance and market reforms. We provide discussions of the results and further implications. Keywords: Stock exchange demutualization, corporate governance, market reforms, factor analysis JEL Classifications: G10, G18, G20